Epithelioid hemangioendothelioma of breast with nodal metastasis masquerading as breast carcinoma: An unusual case with review of literature - Trupti Pai; Tanuja Shet; Asawari Patil; Vani Parmar; Tabassum Wadasadawala; Sangeeta B. Desai (Elsevier, 2021)
Epithelioid Hemangioendothelioma (EHE) is a vascular tumour with intermediate malignant potential which rarely occurs in the breast. We report a unique case of EHE of breast that presented with nodal metastases along with the review of literature. This case was initially misdiagnosed on fine needle aspiration cytology (FNAC) as breast carcinoma; however, histopathology revealed the characteristic short strands and single cell infiltrating pattern by epithelioid cells embedded in a myxohyaline matrix. The typical intracytoplasmic vacuoles with red blood cells were seen in occasional cell hinting at the vascular nature of tumor. Patchy foci of nuclear atypia, pleomorphism and frequent mitoses were seen. Although focal reactivity for AE1/AE3 initially did lead to a differential diagnosis of carcinoma, diffuse positivity for vascular differentiation markers like CD31, CD34 and FLI-1 clenched the diagnosis of EHE. The patient underwent modified radical mastectomy with axillary dissection with post-operative locoregional adjuvant radiation therapy. Till date, with a follow-up of 36 months patient is fine with no event. To conclude EHE can occur in breast and show nodal metastasis like breast carcinomas. However awareness of histologic features with typical immunohistochemistry (IHC) will assist the diagnosis. Inspite of nodal metastasis patient has an uneventful follow up indicating a non-aggressive behavior of this tumor.